Short report: Targeted analysis of whole exome sequencing data in Indian cryptogenic stroke patients - Priya Dev; Jenefer M. Blackwell; Rajiv Kumar; Vijay Mishra; Abhishek Pathak (PLoS ONE, 2026)
Cryptogenic stroke (CS) is an ischemic stroke of unknown cause with increasing incidence in India. Common and rare genetic variants have been associated with the risk of stroke. We carried out targeted analysis of whole exome sequencing on a small cohort of 16 CS patients compared to 16 healthy unaffected relatives to determine whether rare coding variants in genes previously associated with stroke could play a role in India. Variants were filtered for coverage (≥20x) and minor allele frequency (≤0.01). Putative deleterious variants were identified using a range of bioinformatic tools. Targeted analysis was performed by filtering for those variants present in a panel of 220 stroke-related genes. Phenotypes, pathways and cell compartments to which genes carrying putative deleterious (PHRED-scaled CADD scores ≥15) variants belonged were determined using Enrichr. STRING was employed to identify interacting proteins. We identified 17 potentially damaging variants specific to Indian CS patients in 15 genes contributing to phenotypes (e.g., hemorrhage; abnormal blood coagulation; dilated aorta, increased heart weight) and pathways (e.g., platelet degranulation, common pathway of fibrin clot formation; response to elevated platelet cytosolic Ca 2+ ) that were not observed in unaffected relatives. STRING analysis identified 6 genes ( ITGA2B , F13A1 , F5, ATP7A, GLA, ABCC6 ) encoding interacting proteins that could be prioritised for follow-up studies. This should include secondary sequence validation, as well as extended pedigree and functional laboratory-based gene-editing studies to validate the clinical relevance of specific variants to CS. Although limited by small sample size, our study provides novel data on CS in a geographical region and ethnic group not well studied to date.